Physical Activity in New Zealand Preschoolers: Amount, Associations, and Accounts - Oliver, Melody (Auckland University of Technology, 2008)
Improving physical activity (PA) participation is a public health priority in developed and developing countries to curb the substantial and growing prevalence of lifestyle-related diseases. Early childhood may be an especially important time to encourage PA; however, there is a paucity of research in this area. The aim of this research was to contribute to the limited body of work in PA in early childhood by investigating PA measurement approaches in young children and applying this knowledge to determine socio-environmental associations of preschool PA. An initial literature review provided the background for the thesis and determined the approaches taken in the ensuing chapters. A second literature review provided a detailed critique of research specific to PA measurement in early childhood to further inform the empirical studies. Information for the empirical chapters was drawn from three research projects: two studies were completed that assessed tools for objectively measuring PA in young children (pedometers and accelerometers), and these studies informed a final project to quantify associates of PA in a sample of preschool-aged children. Novel and important findings from the preliminary studies were that pedometer accuracy for measuring free-living PA and walking in children aged 3-5 years was poor, especially for pedometers worn at the back of the child, or during slow walking. Furthermore, when investigating the utility of accelerometers (more complex and frequently adopted tools) to quantify PA intensity in preschoolers, their application and use of commonly employed thresholds resulted in systematic underestimation of PA intensity and poor agreement (=0.09) when compared with a direct observation criterion measure. Application of existing accelerometer thresholds to classify PA intensity in preschoolers was therefore likely to yield biased estimates. Given the dearth of robust alternatives, a novel approach was developed to calculate individual activity rates from the raw accelerometer data. To account for over-dispersion in accelerometer counts, daily average activity rates per second were derived for each participant using negative binomial generalised estimating equation (GEE) models with a first-order autoregressive (AR1) correlation structure. These rates were assumed to be exchangeable between days and normally distributed. Potential socio-environmental associates of children’s activity rates and body size were thus assessed using normal GEE models with exchangeable correlation structures. Parental PA and child age were independently and significantly associated with child activity rates (P≤0.04). No relationships between child body size and PA or television (TV) exposure were found. Common approaches to PA measurement and data consideration were challenged in this research and novel robust methods devised utilising contemporary statistical methods. Accelerometer data can be successfully reduced to individual activity rates to mitigate current issues related to objective PA quantification with preschoolers. Parental involvement in preschool PA interventions is worthy of further investigation, and younger children may stand to benefit more from increased activity. Further exploration of the complex interactions between PA, exposure to media, and health outcomes in preschool-aged children is warranted.
Keywords: Physical Activity; Children; Accelerometer; Pedometer; Family; Measure